The puzzle of how higher education learning does in post-COVID-19 pandemic - Nugroho, Iwan (Journal of Socioeconomics and Development, 2023)
The COVID-19 pandemic has exhibited a significant impact on higher education learning. Campus closure or social distancing has been handled by University management, in limited or emergency situations. However, the pandemic has also provided extraordinary lessons learned for the sustainability of higher education in Indonesia. During the post-pandemic period, online learning or blended patterns can be carried out enthusiastically. This paper emphasizes that post-pandemic learning should be strengthened by an evaluation process and a level of satisfaction. The quality assurance mechanism is carried out systematically, especially ensuring the evaluation of online learning and taking continuous improvement actions. The evaluation process is complemented by a customer satisfaction survey involving students, lecturers, and admin staff to ensure the mechanism meets standards. Students should get a favorable atmosphere to involve in learning with the support of adequate lecturer competence, communicative tutorials, easy-to-understand online platforms, and proper class management. JEL ClassificationÂ D80; I18; I23